Impact of the Economical Crisis on the Social Structure of the European Society - Krstić, Zoran G (Sabornost - The Theological Year-book, 2012)
In this report the author presents his own views on the causes of the economic crisis, the impact it has on Serbian society, as well as the possibilities and ways in which the Church can contribute to dealing with the crisis on the larger, European scale. The paper is divided into four parts. The first, called as The Diagnosis and Analysis of the Current Situation, is about generally accepted reasons for the formation of the crisis, and that the crisis is not only economic and financial, but also a profound moral crisis and life values of the European man. The second part is How the Crisis Affects the Serbian Society analyzes the official facts about the Serbian society, especially the youth unemployment. The third part, Different Possibilities of Interpretation of the Crisis analyzes the opinions of some modern sociologists on the pass of crisis, or it is only about the exhaustion of the European model of the welfare state. The final section discusses the role that the Church and believers can have in overcoming the crisis.